Research Trends on Local Potential and Opportunities in Science Education: A Bibliometric Analysis Using VOSviewer - Lestari, Wiwit Yuli; Surtikanti, Hertien Koosbandiah; Rahman, Taufik; Riandi (Journal of Applied Science, Engineering, Technology, and Education, 2024)
Local potential refers to everything a region possesses in various fields, such as natural environment, resource production, culture, society, and other areas. This study aims to conduct a bibliometric analysis by integrating mapping analysis using the VOSviewer program and data collection using the Publish or Perish application. The method used is a bibliometric and quantitative descriptive approach. Data was obtained by searching for the terms "local potential" and "education science" on Google Scholar using the Publish or Perish application, resulting in 560 articles published from 2013 to September 2023. Based on the research, there was an increase in publications during 2013-2017, starting from 3 articles in 2013, 5 in both 2014 and 2015, 10 in 2016, and 75 in 2017. In 2018, there was a decrease to 32 articles, but from 2019 to 2022, there was an increase again, with 69 articles published in 2019, 84 in 2020, 105 in 2021, and 106 in 2022. In 2023, there was a decline to 98 articles. Research on the topic of "local potential" in science education can still be explored further, particularly in under-researched aspects such as “assessment, discovery, ecosystem material, environment literacy, student worksheets (LKPD), local culture, medicinal plants, natural science education, science process skills, science web modules, student worksheets, videos, and wisdom.”